2020
DOI: 10.4103/ajns.ajns_346_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ketofol (combination of ketamine and propofol) and propofol anesthesia in aneurysmal clipping surgery: A prospective randomized control trial

Abstract: Background: The maintenance of hemodynamic stability is of pivotal importance in aneurysm surgeries. While administering anesthesia in these patients, the fluctuations in blood pressure may directly affect transmural pressure, thereby precipitating rupture of aneurysm and various other associated complications. We aimed to compare the effects of ketofol with propofol alone when used as an induction and maintenance anesthetic agent during surgical clipping of intracranial aneurysms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…In addition, the total propofol dose was lower in the ketofol group than in the propofol group, and this may have contributed to the lower incidence of intraoperative hypotension in patients receiving ketofol. Similar to our findings, 2 recently published studies reported superior hemodynamic stability and decreased vasopressor requirement in good grade aneurysmal subarachnoid hemorrhage patients receiving ketofol (ketamine/propofol ratio 1:5) compared with those receiving propofol during craniotomy for aneurysmal clipping 12,13. In another study, ketofol provided superior hemodynamic stability compared with propofol during induction of anesthesia; propofol was more likely than ketofol to be associated with a ≥20% reduction in systolic blood pressure from baseline at 5 minutes (48.8% vs. 12%) and at 10 minutes (67.4% vs. 39%) after induction 14…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, the total propofol dose was lower in the ketofol group than in the propofol group, and this may have contributed to the lower incidence of intraoperative hypotension in patients receiving ketofol. Similar to our findings, 2 recently published studies reported superior hemodynamic stability and decreased vasopressor requirement in good grade aneurysmal subarachnoid hemorrhage patients receiving ketofol (ketamine/propofol ratio 1:5) compared with those receiving propofol during craniotomy for aneurysmal clipping 12,13. In another study, ketofol provided superior hemodynamic stability compared with propofol during induction of anesthesia; propofol was more likely than ketofol to be associated with a ≥20% reduction in systolic blood pressure from baseline at 5 minutes (48.8% vs. 12%) and at 10 minutes (67.4% vs. 39%) after induction 14…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, 2 recently published studies reported superior hemodynamic stability and decreased vasopressor requirement in good grade aneurysmal subarachnoid hemorrhage patients receiving ketofol (ketamine/propofol ratio 1:5) compared with those receiving propofol during craniotomy for aneurysmal clipping. 12,13 In another study, ketofol provided superior hemodynamic stability compared with propofol during induction of anesthesia; propofol was more likely than ketofol to be associated with a ≥ 20% reduction in systolic blood pressure from baseline at 5 minutes (48.8% vs. 12%) and at 10 minutes (67.4% vs. 39%) after induction. 14 A tight brain during craniotomy can further aggravate brain injury because of the greater force required by the surgeon's retractor to achieve an adequate surgical field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For Group OFA [ 13 14 ] : Around 10 ml syringe (labeled as an analgesic agent) contains ketamine (in a dose of 1 mg/kg) diluted with saline to a total volume of 10 ml. Around 50 ml syringe (labeled as an anesthetic agent) contains ketofol (ketamine and propofol in a ratio of 1:5), which contains 8 ml of ketamine (10 mg/ml) and 40 ml of propofol (10 mg/ml) [1 ml of ketofol contains 1.67 mg of ketamine and 8.33 mg of propofol.]…”
Section: Methodsmentioning
confidence: 99%